Clinical Outcome of Fungal Keratitis after Topical use of Injectable Fluconazole - Shahbaz Aslam, Nausherwan Aadil, Wamiq Mehmood, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the clinical outcome of fungal keratitis after topical use of injectable Fluconazole. Materials and Methods: This cross sectional study was conducted in the Department of ophthalmology in Nishtar Medical University, Multan and the duration of this study were from January 2022 to June 2022. Totally 100 patients who were suffering from fungal keratitis were enrolled. The enrolled patients were given topical 2% Fluconazole using Injectable fluconazole 2mg/ml and making it to 2% topical solution. They were also added topical 1% Atropine, lubricant and Cyclosporin A 0.05% was used for corneal melting. Patients were followed after 1 week and 1 month. A predesign questionnaire was used to collect data. Results: Out of total 100 patients, 79 were male and 21 were female with mean age of 38.70 ±9.41 years. The most common age group was 20-35 years and 36-50 years, followed by >50 years of age group. Out of total patients, 69 (69.0%) patients had full recovery of appreciable vision, quality of life and pain related complaints. 30 (30%) patients had no improvement in vision. 1 (1%) patient had worsening of keratitis. Practical implication: This study suggest that topical use of injectable fluconazole is a safe and effective antifungal drug for the treatment of fungal keratitis. So this study will help the ophthalmologist to select better treatment option in order to recover the patients at time. Conclusion: It is concluded that Fluconazole in the form of injection can be a very useful treatment for severe fungal keratitis. Keywords: Fluconazole, Fungal Keratitis, Topical, Injectable, Ophthalmology, Sight-Threatening,